Genetic Structure and Molecular Phylogeny Analysis of Bracon brevicornis Wesmael, a Larval Parasitoid of Coconut Black Headed Caterpillar, Opisina arenosella Walker - Rukhsana, K.; Sebastian, C. D. (Research in Biotechnology, 2015)
Bracon brevicornis (Hymenoptera: Braconidae) a larval parasitoid of O. arenosella and the present study reveals molecular barcoding and phylogeny analysis of B. brevicornis. The adult B. brevicornis gave excellent control of larvae of O. arenosella. We have PCR amplified and sequenced partial fragment of cytochrome oxidase subunit I gene (COI) of B. brevicornis (Genbank Accession: KM 216266) isolated from Kerala and its Ã‚Â phylogenetic status was studied. In Partial COI DNA sequence of B. brevicornis has is 0.16% difference to that of Ã‚Â Habrobracon hebetor (KJ 627789) and 0.48% difference to other Braconinae species (FN 662379, FN 662380, FN 662381, FN 662382). Leucine is the most abundant amino acid in partial COI sequence which is 20.3 % of total amino acids.